2016
DOI: 10.1103/physrevlett.117.215101
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic Electrons Produced by Foreshock Disturbances Observed Upstream of Earth’s Bow Shock

Abstract: Foreshock disturbances -large-scale (∼1000 km to >30,000 km), solitary (∼5-10 per day, transient (lasting ∼10s of seconds to several minutes)) structures 1,2 -generated by suprathermal (>100 eV to 100s of keV) ions 3,4 arise upstream of Earth's bow shock formed by the solar wind colliding with the Earth's magnetosphere. They have recently been found to accelerate ions to energies of several keV 5,6 . One type was found to have a distinct suprathermal electron population with energies >70 keV, which was attribu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 77 publications
(130 reference statements)
5
71
0
Order By: Relevance
“…In ~30% of our events, the maximum energy is larger than 25 keV (minimum SST energy range) in Figure g. In some of the events, energies are hundreds of keV to 700 keV, consistent with the 100–300 keV events reported by Wilson et al [] (their events are shown in green in Figure g).…”
Section: Statistical Results Of Electron Energizationsupporting
confidence: 90%
See 1 more Smart Citation
“…In ~30% of our events, the maximum energy is larger than 25 keV (minimum SST energy range) in Figure g. In some of the events, energies are hundreds of keV to 700 keV, consistent with the 100–300 keV events reported by Wilson et al [] (their events are shown in green in Figure g).…”
Section: Statistical Results Of Electron Energizationsupporting
confidence: 90%
“…For example, diffusive shock acceleration at shocks requires particles that have large initial energy, but where such particles obtain this energy is still unknown (the so‐called “injection” problem) [ Jokipii , ]. We have shown that foreshock transients often preaccelerate particles before they interact with the shock and bring them toward the bow shock supporting previous results [e.g., Liu et al ., ; Wilson et al ., ]. Foreshock transients could in principle form everywhere throughout the universe upstream of shocks, and thus, they may be quite important for addressing the injection problem.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…This study, along with other recent observations (e.g., Liu, Hietala, et al, ; Liu, Angelopoulos, & Hietala, ; Liu, Angelopoulos, Hietala, & Wilson, ; Liu, Lu, et al, ; Wilson et al, ), demonstrates foreshock transients' ability to accelerate particles, implying that they have an important role in shock acceleration like providing a source for diffusive shock acceleration and repopulating foreshock ions, and potentially contributing to enhanced magnetospheric fluxes. These topics deserve more attention and multipoint studies in the future.…”
Section: Discussionsupporting
confidence: 79%
“…Wilson et al . [] also reported that electrons in the foreshock transients can be accelerated to 100–300 keV. A recent statistical study shows that although the electron energy estimates of the suprathermal component in foreshock transient cores is almost always higher than in the background foreshock, an ion mean energy enhancement in the core is only occasionally observed [ Liu et al ., ].…”
Section: Introductionmentioning
confidence: 99%